Potensi Produksi Enam Hibrida Jagung pada Ultisol di Provinsi Bengkulu - Suprijono, Eko; Rustikawati, Rustikawati; Romeida, Atra; Gustian, Meko (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2015)
Ultisol is one of marginal land type quite extensively presence in Indonesia, including the province of Bengkulu. The use of varieties tolerance to acidity stress is the best manner to utilize of this type of land with relatively low cost and environmentally friendly. The objective of this research was to evaluate theyield potential of six maize hybrids developed to soil acidity tolerance. The experiment was conducted at the Experimental Farm Medan Baru, Kandang Limun Village, Muara Bangkahulu District, Bengkulu City, from August to November 2015. The experiment was arranged in a randomized completely block design with four replications. As the treatment were newly developed maize hybrids, namely CT5, CT8, CT9, CT13, CT14 and CT15. The variables measured were cob length, cob diameter, 100-seed weight and the estimated yield/ha. Qualitative variables supporting to corn yield were the cob position, seed color, seed type and seed row arrangement. The results indicated that the hybrid CT8 showed the highest estimated yield in Ultisol among hybrids evaluated, with the estimation of 6.5 tons per hectare. Qualitatively, theseeds of hybrid CT8 were a horse tooth type, pale yellow color, and stright line arrangement.